PENGARUH MODEL QUANTUM LEARNING TERHADAP KEMAMPUAN PEMAHAMAN MATEMATIS SISWA KELAS IV SDN RAWALELE DAWUAN - Muhamad Faizal; Nurlaela; Lili Herawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2022)
This research is motivated by the low ability of mathematical understanding of grade IV students. The purpose of this research is to find out how far the influence of the quantum learning model has on the ability to understand mathematics. The samples in this study were 19 students from Rawalele Elementary School, class IV A, and 19 students from class IV B. The data in this study were collected through written tests and documentation. The method used is a quasi-experimental research design using The Nonequivalent Pretest Posttest Control Group Design. Based on the processing and analysis of research data, namely: (1) The quantum learning model can improve students' mathematical understanding abilities in the experimental class by using the quantum learning model and the control class with conventional models in class IV SDN Rawalele. Experimental class students (using the quantum learning model) have an average N-Gain of 0.57, whereas with the criteria of "moderate" improvement while the average N-Gain increase in the control class (not using the quantum learning model) is 0.20 with criterion of “low” improvement. (2) The quantum learning model influences the ability to understand mathematics. Based on the results of the hypothesis test (t-test) posttest data of the experimental and control classes, the results of the t-test (ttable) were 2.024 while the tcount was 2.381 so it was stated that tcount ≥ ttable which means H0 is rejected and H1 is accepted. Thus there is an influence on the quantum learning model on students' mathematical understanding abilities (3) The quantum learning model has a major effect on students' mathematical understanding abilities; (3) The results of the effect size test obtained d, namely 1.82, with the criteria of "large". So the quantum learning model has a major influence on students' mathematical understanding abilities with the subject of the concept of multiples and factors of a number.